2013
DOI: 10.1111/j.1756-1051.2012.00054.x
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic implications of pollen exine morphology in infrageneric classification of Scutellaria (Lamiaceae)

Abstract: and M. Hasani-Nejad, Research Inst. of Forests and Rangelands, PO Box 13185-116, Tehran, Iran. Scutellaria L. in Lamiaceae subfamily Scutellarioideae is a subcosmopolitan genus with about 360 species. According to the latest subgeneric classifi cation, two subgenera are recognized: S. subgen. Scutellaria and S. subgen. Apeltanthus . We studied pollen grains from 29 species of Scutellaria belonging to both subgenera and from both the Old and the New World to evaluate their taxonomic importance for the infrag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…17) Lavandula dentata and Lavandula pubescens (Table 2, Figs. 3 and 8, examined by LM) The results of the first three species agree with that mentioned by Kose et al, 2011, Dinç et al, 2009 and Jamzad and Hasani-Nejad (2013). The surface ornamentation of the last two species is mentioned as reticulate under SEM (Evert and Eichhor, 2013) which also confirmed with our findings in this tudy.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…17) Lavandula dentata and Lavandula pubescens (Table 2, Figs. 3 and 8, examined by LM) The results of the first three species agree with that mentioned by Kose et al, 2011, Dinç et al, 2009 and Jamzad and Hasani-Nejad (2013). The surface ornamentation of the last two species is mentioned as reticulate under SEM (Evert and Eichhor, 2013) which also confirmed with our findings in this tudy.…”
Section: Resultssupporting
confidence: 92%
“…Kose et al (2011) reported that the granulate or reticulate type of exine ornamentation in Ajuga species may be is useful in segregating the species within the genus. Hasani-Nejad et al (2011) and Jamzad and Hasani-Nejad (2013) showed that the exine ornamentation could be used as a taxonomic feature below generic level classification of Scutellaria. Osman (2012) in his study of Ballota species in Egypt mentioned that pollen characters were very useful in the separation of the species.…”
Section: Introductionmentioning
confidence: 99%
“…Ziziphora clinopodioides has a large geographical distribution and represents high morphological diversity in Iran and adjacent countries. Our investigations have revealed that the pollen grain morphology can be useful in clarifying the infra-specific classification (Jamzad and Hasani-Nejad 2014, Keshavarzi et al 2008, Selvi et al 2013, Tabaripour et al 2018, such as the ornamentation of the pollen grains have valuable morphological characteristics to solve taxonomic problems of some subspecies in Ajuga. The sculpture of A. chamaepitys subsp.…”
Section: Discussionmentioning
confidence: 98%
“…Species of Taiwanese skullcaps, which have been suggested to be rapidly evolving [ 9 ], are morphologically varied in petal colors and vegetation forms ( Table 1 ). High interspecific variation in the pollen size and exine, which are major taxonomic characters in Scutellaria [ 44 ], and which are regulated by MYB16 , could be related to the pollinator shift between different Scutellaria species [ 43 ]. The positive sites 134Y in MYB11 and 196C in MYB16 , both of which had high posterior probabilities, are located within the DNA-binding domain.…”
Section: Discussionmentioning
confidence: 99%